Association between fibrinogen-to-albumin ratio and bone metabolism markers (β-CTX and P1NP) in Chinese individuals with osteoporotic fracture: a cross-sectional investigation - Li-long Feng; Ke Lu; Chong Li; Min-zhe Xu; Yao-wei Ye; Yi Yin; Hui-qiang Shan (BMC Musculoskeletal Disorders)
Abstract Objective Research on the link between inflammatory indicators and markers of bone metabolism is currently lacking, especially the interaction between Procollagen type 1 N-terminal propeptide (P1NP), the β-C-terminal telopeptide of type 1 collagen (β-CTX), and the fibrinogen-to-albumin ratio (FAR). This study intends to fill that knowledge gap by investigating the possible link between inflammatory indicators and bone metabolism. Methods This observational study included 718 individuals diagnosed with osteoporotic fractures from Kunshan Hospital Affiliated to Jiangsu University between January 2017 and July 2022. After accounting for several confounders, the independent connection between FAR levels and β-CTX and P1NP was investigated via Generalized Estimating Equations (GEE). On top of that, we used a generalized additive model (GAM) to find any non-linear correlations, and a two-piecewise linear regression model to find the threshold effects in the smoothing curves that came out of it. To ensure the aforementioned result was stable, a subgroup analysis was carried out. Results The results showed a positive linear correlation between FAR and β-CTX [β = 1.077, 95% confidence interval (CI): 0.24 to 1.92, P = 0.012]. The study’s findings demonstrated that FAR and P1NP fit curves in an inverted U-shaped pattern, and an inflection point K = 0.0685 for FAR was detected. P1NP showed a positive correlation with FAR below the inflection point (β = 306.10, 95% CI: 47.37 to 564.83, P = 0.021), and a negative correlation with FAR beyond the inflection point (β = -117.57, 95% CI: -231.34 to -3.80, P = 0.043). The subgroup analysis revealed that women had a more significant association between FAR and β-CTX in women than in men. Conclusions The results provide useful insights into the potential association between FAR and markers of bone metabolism. The study may provide a novel clinical implication by introducing FAR as a potential reference indicator for assessing bone health, offering a cost-effective and conveniently obtainable biomarker to monitor inflammation to improve bone metabolism in the treatment of osteoporosis.